The combination treatment of oncolytic adenovirus H101 with transcatheter arterial embolization sequential thermal ablation for hepatocellular carcinoma: a retrospective study - Jing, Changyou; Zhu, Tong; Zhang, Yonghong; Li, Jianjun (Frontiers in Oncology, 2025)
Background & AimsRecombinant human adenovirus type 5 (H101) was demonstrated to enhance the efficacy of transcatheter arterial embolization (TAE) for hepatocellular carcinoma (HCC). This study aims to analyze the efficacy and safety of oncolytic adenovirus H101 combined with TAE sequential thermal ablation in HCC.MethodsThis single-center retrospective study evaluated the progression-free survival (PFS) and overall survival (OS) of HCC patients who received H101 combined with TAE sequential thermal ablation therapy from July 2015 to January 2022. Adverse reactions during treatment were recorded.ResultsA total of 55 HCC patients were included, with a median follow-up of 39 months (range: 10–106 months). During the follow-up period, disease progression was observed in 43 of 55 patients, and 22 of the 55 patients died. The median OS and PFS time were 77 and 12.3 months, respectively. The one-, two-, and three-year OS rates were 94.5%, 86.3%, and 77.3%, respectively. The PFS rates at one, two and three years were 56.4%, 26.3% and 20%, respectively. Multivariate analysis revealed that the diameter was independent predictors of PFS (P = 0.023). No patient experienced a serious adverse event, or a fatal or disabling event, due to the injection of oncolytic virus.ConclusionThis study suggests that HI01 combined with TAE sequential thermal ablation is both safe and effective for HCC, warranting further investigation through prospective randomized controlled trials.